DENOTATION, CONNOTATION, AND MYTH THROUGH VERBAL AND NON-VERBAL SIGNS ON REPRESENTATION OF IDENTITY IN THE BIG SIX PREMIERE LEAGUE CLUB LOGOS - Arif Lutfi Rohmani; Suyatman, Ujang; Sakinah, R. Myrna Nur (Universitas PGRI Palembang, 2025)
This study investigates the verbal and non-verbal elements within the logos of the